Grunge Typography Book Design from David Carson's Work for Young Graphic Designers - Dhani Agustinus; Sujendro Hery Nugroho; Alexander Rachel Deffarani Diwara (Jurnal Info Sains : Informatika dan Sains, 2026)
This study aims to design a grunge typography book based on David Carson's work aimed at young graphic designers as a guide to understanding and implementing innovative and experimental grunge typography styles. The research method uses a qualitative type with a Research and Development (R&D) approach, which includes pre-production, production, and post-production stages. This book is designed by utilizing a distinctive color scheme, unique typography choices, and a small landscape format to optimize the visual appearance. The creative process involves the use of applications such as Procreate and professional design software such as Adobe Photoshop and InDesign. Promotion is carried out through digital media, such as Instagram and Tokopedia, as well as print media, including posters and stickers. The results of this study produce a book that not only reflects the aesthetics of the grunge style but also serves as a reference for young graphic designers to develop creative, bold, and unique works.